2020
DOI: 10.3390/ijerph17228400
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Mood and Cognitive Performance before and after a 100 km Nighttime Ultramarathon Run

Abstract: Ultramarathons are becoming an increasingly popular endurance sport. Year after year, the demands on athletes’ skills and endurance increase. Ultramarathons are particularly taxing on athletes’ psychological functioning. This study assessed the relationships between taking part in a nighttime ultramarathon and changes in mood and cognitive functioning. The study included 20 experienced runners aged 26–57 (M = 37.29; SD = 7.94) who had M = 7.08, SD = 5.41 (range 3–44) years of experience running. There were 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 39 publications
(55 reference statements)
0
8
1
Order By: Relevance
“…Owing to the influence of extreme physical and psychological demands of participating in an ultra-marathon event, we expected cognitive performance would decrease post-race. The current study contradicts previous work displaying prolonged physical fatigue may in fact result in a reduction of psychomotor and neuromuscular function; however, it does not necessarily have to be associated with mental fatigue and a reduction in cognitive functioning ( Wollseiffen et al, 2016 ; Krokosz et al, 2020 ). These studies showed no significant change in cognitive performance following prolonged exercise suggesting that enhanced physical conditioning may have an impact on the cognitive performance post-race; however, further empirical evidence is required.…”
Section: Discussioncontrasting
confidence: 99%
“…Owing to the influence of extreme physical and psychological demands of participating in an ultra-marathon event, we expected cognitive performance would decrease post-race. The current study contradicts previous work displaying prolonged physical fatigue may in fact result in a reduction of psychomotor and neuromuscular function; however, it does not necessarily have to be associated with mental fatigue and a reduction in cognitive functioning ( Wollseiffen et al, 2016 ; Krokosz et al, 2020 ). These studies showed no significant change in cognitive performance following prolonged exercise suggesting that enhanced physical conditioning may have an impact on the cognitive performance post-race; however, further empirical evidence is required.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies assessing cognitive performance in ultra-marathon field studies have used a plethora of diverse tools to assess cognitive performance. These include language control [ 26 ], problem solving [ 13 ], concentration and attention [ 13 , 16 , 17 ], reaction times [ 11 , 15 ] and executive function [ 11 , 12 , 15 , 26 ], with the latter three most frequently studied. The Stroop task has frequently been used as a measure of executive function in studies of cognitive performance in endurance events (two ultra-marathons [ 11 , 12 ] and one adventure race [ 27 ]) and in laboratory studies looking into the effects of sleep deprivation on athletes [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…These include language control [ 26 ], problem solving [ 13 ], concentration and attention [ 13 , 16 , 17 ], reaction times [ 11 , 15 ] and executive function [ 11 , 12 , 15 , 26 ], with the latter three most frequently studied. The Stroop task has frequently been used as a measure of executive function in studies of cognitive performance in endurance events (two ultra-marathons [ 11 , 12 ] and one adventure race [ 27 ]) and in laboratory studies looking into the effects of sleep deprivation on athletes [ 28 ]. Reaction time has been used as an outcome measure both in field studies and in laboratory studies examining the impact of sleep deprivation in athletes [ 5 , 15 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations